oceanic corpo-graphies, refugee bodies and the making and unmaking of waters - Perera, Suvendrini (Palgrave Macmillan, 2013)
This essay considers the challenges that the gendered and raced transnational subaltern refugee subject poses to the order of ‘the liberal state’ and ‘the liberal subject’, and argues that the latter are bound up in complex ways with entrenched understandings of the ocean as elementally distinct from land. This distinction, constituted by the freedom of the sea-going individualist liberal subject, invariably raced as white and gendered as male, to range across the waves in search of new worlds to conquer, is one that is continually reproduced both in popular culture's contemporary sea romances, and in the spatial and legal demarcations of the nation and its limits. In the diverse forms of traffic flowing from south to north, the historical oceanic mobility of this unfettered liberal subject (always shadowed and weighted down by its invisible freight of non-white bodies) now meets the transversal movements of the contemporary transnational subaltern as complex subject. Through the narratives of two refugees to Australia, the article traces the possibilities of an embodied refugee poetics for inscribing new geographies across the global borderlands.